2023
DOI: 10.3389/fimmu.2023.1147520
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid WIN55,212-2 reprograms monocytes and macrophages to inhibit LPS-induced inflammation

Abstract: IntroductionChronic or uncontrolled activation of myeloid cells including monocytes, macrophages and dendritic cells (DCs) is a hallmark of immune-mediated inflammatory disorders. There is an urgent need for the development of novel drugs with the capacity to impair innate immune cell overactivation under inflammatory conditions. Compelling evidence pointed out cannabinoids as potential therapeutic tools with anti-inflammatory and immunomodulatory capacity. WIN55,212-2, a non-selective synthetic cannabinoid ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…In line with this evidence, recently, we have found that CBD profoundly affects some key human neutrophil functions, showing a powerful anti-inflammatory profile [10,11]. In addition, it was recently shown that the exogenous cannabinoid WIN55212-2 is able to affect the T cell response [18] or modulate the functions of monocytes and macrophages inhibiting LPS-induced inflammation [19], corroborating our and other studies suggesting that cannabinoids, through complex and varied mechanisms, can modulate the immune response and, therefore, probably be used for different therapeutic purposes in addition to what at present is sustained.…”
Section: Discussionmentioning
confidence: 53%
“…In line with this evidence, recently, we have found that CBD profoundly affects some key human neutrophil functions, showing a powerful anti-inflammatory profile [10,11]. In addition, it was recently shown that the exogenous cannabinoid WIN55212-2 is able to affect the T cell response [18] or modulate the functions of monocytes and macrophages inhibiting LPS-induced inflammation [19], corroborating our and other studies suggesting that cannabinoids, through complex and varied mechanisms, can modulate the immune response and, therefore, probably be used for different therapeutic purposes in addition to what at present is sustained.…”
Section: Discussionmentioning
confidence: 53%
“…Dendritic cells (DCs) are professional antigen-presenting cells that play a key role in the generation of pTregs. Immature or mature DCs conditioned by pathogen-derived molecules, FOXP3 + Tregs, and exogenous signals such as vitamin D3 metabolites [26], adenosine, histamine [27,28], retinoid acid, mannan [29,30], cannabinoids [31][32][33][34], or heparan sulfate-related proteoglycan [35], promote the generation of Tregs through mechanisms involving soluble molecules such as TGF-β, retinoic acid, the enzyme indoleamine 2,3-deoxygenase (IDO), and surface-binding co-stimulatory molecules such as programmed death ligand 1 or inducible co-stimulatory molecule ligand. In addition, plasmacytoid DCs (pDCs) might well display intrinsic tolerogenic capacity to promote Tregs [36].…”
Section: Immunobiology Of Tregsmentioning
confidence: 99%
“…WIN55212-2 is a potent full agonist of the CB 1 receptor and has been used in experimental as well as clinical studies [33][34][35][36]. Mice treated with WIN55212-2 have been shown to have a significant reduction in pain, making it a plausible analgesic [37].…”
Section: Grabecb20 Assays For Cb1r Agonistsmentioning
confidence: 99%